Outcome of group physical therapy treatment for non-specific low back pain patients can be predicted with the cross-culturally adapted and validated Hungarian version STarT back screening tool. Issue 8 (10th April 2022) - Szita, Julia; Kiss, Laszlo; Biczo, Adam; Feher, Katalin; Varga, Peter P.; Lazary, Aron
Abstract: Purpose: The STarT Back Tool was developed to identify the specific modifiable prognostic factors for non-specific low back pain and to classify the patients into risk groups; low, medium and high risk of chronicity. Applied therapeutic approaches often involve group physical therapy. The aim of this study was the cross-cultural adaptation and validation of the Hungarian version of the STarT Back Tool and to investigate the predictive ability for global treatment outcome. Materials and methods: A prospective cohort study ( N = 133) was carried out involving non-specific low back pain patients. Internal consistency, construct validity, reliability and prognostic discriminative ability have been investigated. After 3 months of treatment global outcome was evaluated. Results: A 2-factor structure was found, with moderate internal consistency (Cronbach α = 0.89 for the total and psychosocial subscale 0.62). Between the Hungarian STarT Back Tool, the Oswestry Disability Index, leg pain, low back pain, Tampa Scale for Kinesiophobia, Fear Avoidance Beliefs Questionnaire and the physical subscale of the quality of life questionnaire, significant good to excellent- correlation was found ( r > 0.41). The test-retest analysis showed excellent reliability (Intraclass Correlation Coefficient = 0.93) with standard error measurement being 0.49 (minimal detectable change = 1.37). The Area Under the Curve for baseline STarT Back Tool scores was 0.7 and 0.8 for global treatment outcome and distress, respectively. The Area Under the Curve for global treatment outcome versus STarT risk groups proved to be 0.76 representing adequate discriminative ability. Conclusion: The successful cross-cultural adaptation was followed by the validity analysis and as a result the Hungarian version of the STarT Back Tool proved to be a reliable and valid tool in the identification of risk groups of chronicity for patients with low back pain. Patients allocated to the high-risk group were more likely experiencing poor outcome at 3 months follow up, thus it can be used to predict outcome if treated with group physical therapy. Implication for rehabilitation: Low back pain is a multifactorial disease where physical and psychosocial risk factors play a role in the development and prognosis of the disease. The STarT-H can be considered as a reliable, valid measurement tool in the identification of risk groups of chronicity for patients with low back pain. Clinical relevance of the STarT-H is that it can be used to stratify patients into risk groups of chronicity in different Hungarian speaking healthcare settings. According to our findings the STarT-H can also be applied to predict global treatment outcome in low back pain patients if treated with group physical therapy.